Neurocisticercose: aspectos epidemiológicos, manifestaçōes clínicas e resposta terapêutica dos pacientes atendidos em um hospital de referência do Ceará - Silva, Francisco Vinícius Ferreira da (2019)
Introduction: Neurocysticercosis (NCC) is a disease caused by infection of Taenia solium cysticerci in the central nervous system (CNS). The total number of people suffering from the disease, including symptomatic and asymptomatic cases, is estimated at 2.56 - 8.30 million in the world. NCC treatment consists of antiparasitic medications such as albendazole or praziquantel and corticosteroids with the aim of reducing the inflammatory process unleashed by the death of cysticerci. Objective: To identify the epidemiology, clinical manifestations and therapeutic response of individuals with neurocysticercosis treated at a reference unit for the treatment of infectious diseases in the State of Ceará, Hospital São José (HSJ), in the period 2005-2017. Material and Methods: This is a quantitative, cross-sectional and descriptive study. Retrospective data from the medical records of patients with NCC were collected from the Medical and Statistical Archive Service (SAME) of the HSJ, through a standard form. Results: 143 medical records of patients with NCC treated at the HSJ were selected, and their origin was distributed throughout the territory of Ceará, with the highest number of cases in the city of Fortaleza (44%). Of the 143 patients, 99.3% were hospitalized, with an average of 1.69 hospitalizations. The main symptoms presented were seizures (80.4%), headache (70.6%), cognitive deficit (25.1%) and paresthesia of lower limbs (18.8%). The mean time individuals took from diagnosis to treatment was 8.6 months. Albendazole was the drug most used by patients (99.3%) and 29.3% (42) of them did not respond well. The most frequent doses of albendazole were 800mg (48.2%), 1200mg (29.3%), 400mg (4.8%) and other doses (16.7%). The mean time used in the treatment of NCC with albendazole was 20.6 days. Conclusion: The NCC has a high prevalence in the municipality of Ceará and the therapy with albendazole and praziquantel is limited, given the need for several cycles and higher doses of the drug, which are often not well tolerated by the intense inflammatory reaction in the CNS. Further studies need to be performed to identify new therapies for NCC.